The Influence of Al-Qur’an Memory Level and Learning Motivation on Student Academic Achievement - Siti Rohmatin Nur Ifana (Universitas Muhammadiyah Yogyakarta, 2023)
The ability to memorize the Qur'an affects one's cognitive intelligence. The students felt the influence of the program provided by UNIRES, which gave birth to a feeling of difficulty in dividing their time between memorizing the Al-Qur'an and following the lecture process in achieving their academic achievements. This situation is also influenced by the motivation to learn. The purpose of this research is; 1) To find out the level of student Al-Qur'an memorization, 2) To find out student learning motivation, 3) To find out student academic achievement, 4) To find out